Antitumor and adjuvant effects of phagelysates of E.coli in mice with Ehrlich carcinoma - Gambashidze, K.; Khorava, P.; Azaladze, T.; Kalandarishvili, K.; Jaiani, E.; Lasareishvil, B.; Azaladze, A.; Tediashvili, M. (Experimental Oncology, 2012)
Aim: To augment anti-tumor host response and overcome the tumor-induced immunosuppression is of paramount importance especially when patient is subjected to radio-/chemotherapy and immune system suffers significantly. Various immunological methods have been employed as supplemental antitumor therapies. We were aimed to investigate the antitumor potential of phagelysates of gram-negative bacteria and their adjuvant effects for conventional chemotherapy in experiment. Methods: Bacterial phagelysates of E.coli and purified suspensions of corresponding Un bacteriophage were obtained by standard methods of phage research. Experiments were carried out on BL57C/6J mice bearing transplanted Ehrlich carcinoma. Different regimens of phagelysate administration (0,5 ml E. coli phagelysate, 3/8 times with 5 day intervals) and conventional chemotherapy (combination of Doxorubicin 60 mg/m2, Cyclophosphan 800 mg/m2, Ftoruracil 600 mg/m2, 3 times with 21 day intervals) were tested. Treatment efficacy was evaluated by tumor growth inhibition percent, index of malignant growth, lifespan and survival percent. Results: Experiments have shown that application of optimal doses of E. coli phagelysate can be well tolerated in mice. No stimulation or support of malignant growth was observed. E. coli phagelysate exhibited significant anticancer effect and adjuvant efficacy. Cancer development was delayed in 65% of inoculated animals in the test group. E. coli phagelysate inhibited tumor growth by 80–90% without apparent side effects. The mice survival was prolonged twice and more. On 65th-69th days of tumor growth in 13% animals complete regression of neoplasms was registered. Application of phagelysates in combination with chemotherapy significantly increased antitumor efficacy of conventional chemotherapeutic drugs. Conclusion: Application of bacterial phagelysates can be considered as promising novel strategy in cancer therapeutics.